1975
DOI: 10.1139/x75-036
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of American Elm via Cell Suspension Cultures

Abstract: American elm was propagated from callus derived from cell suspension cultures. Suspensions, established from callus, were plated onto agar where, after transfer to a simpler defined medium over 18 months, shoots were produced. Maintenance of high auxin levels yielded roots but no shoots. Shoots were removed from the callus, were treated briefly with indole-3-butyric acid, and transferred to a sphagnum moss – sand mixture for rooting. Other than the absence of cotyledons, plants from callus were comparable to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Regeneration of American elm shoots had been reported from hypocotyl-derived cell suspension cultures (Durzan & Lopushanski 1975), hypocotylderived callus cultures (Karnosky et al t982) and cryogenically preserved callus (Ulrich et al 1984). Most recently, Bolyard et al (1991) reported shoot regeneration on leaves from 6-mont.h-old American elm seedlings.…”
Section: Introductionmentioning
confidence: 98%
“…Regeneration of American elm shoots had been reported from hypocotyl-derived cell suspension cultures (Durzan & Lopushanski 1975), hypocotylderived callus cultures (Karnosky et al t982) and cryogenically preserved callus (Ulrich et al 1984). Most recently, Bolyard et al (1991) reported shoot regeneration on leaves from 6-mont.h-old American elm seedlings.…”
Section: Introductionmentioning
confidence: 98%
“…However, this strategy can only be initiated after the establishment of efficient protocols for plant regeneration from cells and tissues of elm trees (Fenning et al 1996a). Protocols of this type have already been developed from differentiated explants (Fink et al 1986;Dorion et al 1987;Bolyard et al 1991;Fenning et al 1993;George and Tripepi 1994;Cheng and Shi 1995;Kapaun and Cheng 1997;Ben Jouira et al 1998), from callus (Karnosky et al 1982), from suspension cultures (Durzan and Lopushansky 1975) and from protoplasts (Sticklen et al 1986;Dorion et al 1994) of some species and clones of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…The buds used were undoubtedly adult phase since they were harvested from trees that were 10 to 20 years. Ulmus americana L. has been regenerated from callus, but in both cases this callus was initiated from seedling tissues [3,16]. The demonstration that callus cultures of elm can undergo organogenesis is important, since one of the long term goals of this research is to be able to regenerate plants from protoplast derived callus.…”
Section: Introductionmentioning
confidence: 99%